2015
DOI: 10.5603/fhc.a2018.0001
|View full text |Cite
|
Sign up to set email alerts
|

RSK1 promotes murine breast cancer growth and metastasis

Abstract: We provide evidence that RSK1 supports tumor growth and metastatic spread in vivo as well as in vitro migration and survival in non-adherent conditions. Further studies of RSK1 involvement in TNBC progression may substantiate our findings, laying the foundations for development of anti-RSK1-based therapeutic strategies in the management of patients with TNBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…ESR1 is a telomerase activating factor that binds to the hTERT promoter and its role in EC is well established [ 47 , 217 , 225 ]. The identification of RPS6KA1 and WFS1 is interesting as previous studies have reported their role in the promotion of tumour progression and metastasis in various cancers [ 226 , 227 , 228 , 229 ]. The role of ANAPC4 in cancer has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…ESR1 is a telomerase activating factor that binds to the hTERT promoter and its role in EC is well established [ 47 , 217 , 225 ]. The identification of RPS6KA1 and WFS1 is interesting as previous studies have reported their role in the promotion of tumour progression and metastasis in various cancers [ 226 , 227 , 228 , 229 ]. The role of ANAPC4 in cancer has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…c‐Jun, PRAS40, RSK‐1, and RSK‐2 are common phosphokinases in cancer progression 35–37 . However, by western blot analysis, we found the total protein levels of c‐jun also changed and the proportion of p‐c‐jun/c‐jun, p‐PRAS40/PRAS40, p‐RSK‐1/RSK, and p‐RSK‐2/RSK does not change significantly.…”
Section: Discussionmentioning
confidence: 67%
“…c-Jun, PRAS40, RSK-1, and RSK-2 are common phosphokinases in cancer progression. [35][36][37] However, by western blot analysis, we found the total protein levels of c-jun also changed and the proportion of p-c-jun/c-jun, p-PRAS40/PRAS40, p-RSK-1/RSK, and p-RSK-2/RSK does not change significantly. c-Myc is an established proto-oncogene that can promote cell survival and proliferation, and cyclin D1 is an important cell cycle regulator.…”
Section: Discussionmentioning
confidence: 99%
“…protein S6 kinase (RPS6K) (Li et al, 2012;Czaplinska et al, 2018). The RPS6K family is reported to be involved in a lot of pathways, which are important for tumor occurrence and progression (Hajj et al, 2020;Lai et al, 2020;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%